Studi Tegangan Tembus Minyak Transformator - I Nyoman Oksa Winanta; Anak Agung Ngurah Amrita; Wayan Gede Ariastina (Jurnal SPEKTRUM, 2019)
This study aims to identify the effect of changes in temperature, water content, andelectrode gap on the breakdown voltage of transformer oil. The transformer oil used in this studywas Shell Diala-B and Nynas oil. Testing the effect of temperature was carried out attemperature variation of 280 C to 810 C, the effect of water content was carried out withvariations ranging from 11 ppm to 31 ppm, and the effect of electrode gap was carried out invariation ranges between 1.2 mm to 2.5 mm. Breakdown voltage testing method useshemispherical electrodes according to IEC 60156 standard of 1995. The results of the studyshow that the higher the temperature, the higher the breakdown voltage of transformer oil. Thehighest breakdown voltage in Nynas oil occurs when the temperature is 810 C which is equal to59.27 kV. The results also show that the higher the water content, the breakdown voltage islower. The highest breakdown voltage in Shell Diala-B oil occurs with a water content of 11 ppmwhich is equal to 61.35 kV. Also the greater the electrode gap, the greater the breakdownvoltage. The highest breakdown voltage in Nynas oil occurs with the gap of electrode 2.5 mmwhich is equal to 60.02 kV.